Digital Simulation as Learning Aid for Heat Flow in Solid Theoretical Understanding - Inge Magdalena Sutjahja; Sufiyah Assegaf; Surjamanto Wonorahardjo (JPSE (Journal of Physical Science and Engineering), 2020)
Understanding the physical phenomena is extremely aided by digital simulations for understanding physical phenomena that occur, especially for students in the digital era and in this new-normal period. This paper describes heat conduction in solids using the Energy2D program, starting from general formulations for heat conduction from conductors to general solids that show the mechanism of heat conduction as a diffusion process. The thermal diffusivity parameter determines heat diffusion as the ratio between thermal conductivity and multiplication between density and thermal capacity. From the practical side, heat conduction is ordinary using thermal resistance (R-value) that combines the dimensions of the material in the direction of heat flow and thermal conductivity. By taking an analogy with Ohm's law for electrical circuits, it can be determined the equivalent resistance of several thermal resistance of the material that is composed in series or parallel. A good understanding of the heat transport process in buildings is needed for the development of technologies required for the comfort of human life and energy conservation. DOI: http://dx.doi.org/10.17977/um024v5i12020p011